A Formação de Redes como Alternativa para o Desenvolvimento Regional - Andrea Carla Bordignon Lunedo (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2018)
The formation of networks between companies, government, financial and educational institutions as an organizational framework, beyond society in general, contribute to regional development. The target of this research was to analyze this network structure, as an alternative of regional development and the relations the actors involved in the process establishes with society in general. The cities comprised by the Regional Development Agency (ADR) of Quilombo – Santa Catarina are object of this study. In documentary analysis and interviews it was possible to realize that the Quilombo ADR has a relevant role in obtaining and directing the needs of cities that ADR is composed of acting as a link between town council and the state government. However, the interactions between government, companies or business entities, educational and financial institutions still needs to be improved. On the other hand, entrepreneurs and associations actively try to obtain alternatives for business competitiveness and consequently the development of the region. The Santa Catarina State Government Program – “Crescendo Juntos” –, is contributing to the participation of all actors in the process of the formation of regional networks, being the State stimulating actor, besides helping, mainly, with the educational and financial institutions.